Serodiagnosis of Severe Acute Respiratory Syndrome Corona Virus (ANTI-SARS-CoV-2) Antibody in Blood Donors in Surabaya, Indonesia - Evy Diah Woelansari; Retno Sasongkowati (Humanistic Network for Science and Technology (HNST), 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). So far, the incidence of direct blood-borne transmission is not widely known. This is because the viremia of SARS-CoV-2 virus infection is very small, between 2-3 days after infection. Immunoglobulin M (IgM) is an antibody that is formed in the early days of a person being infected with the virus, which is around the third day and can persist in the blood for up to 3-4 months after infection. The purpose of this study was to perform serodiagnosis of SARS-CoV-2 antibodies in blood donors in Surabaya. The type of research used is an experimental laboratory with an exploratory research design. The research sample consisted of 100 donor blood samples from UTD PMI Surabaya. Rapid diagnostic test examination at the Immunology Laboratory, Medical Laboratory Technology Department, and the Immunoserology Laboratory of BBLK Surabaya, Indonesia for antibody titer examination using the ELISA method in May 2022. Results of antibody analysis against SARS-CoV- 2 in blood donors in Surabaya by 58% (Cut Off Index = 0.1569), so further research is needed on factors that can affect the formation of antibodies. Keywords: SARS-CoV-2 IgG; SARS-CoV-2 IgM; blood donor